TÜRKÇE VE TÜRK DİLİ VE EDEBİYATI ÖĞRETMENİ ADAYLARININ ÖĞRETMENLİK MESLEĞİNE İLİŞKİN TUTUMLARININ ÇEŞİTLİ DEĞİŞKENLER AÇISINDAN İNCELENMESİ (KAFKAS ÜNİVERSİTESİ ÖRNEĞİ). - Bozkirli, Kürşad Çağrı; Er, Onur (Electronic Turkish Studies)
The aim of this study is to examine the attitudes of Turkish teacher candidates and Turkish Language and Literature teacher candidates, who attend to formation program, toward teacher profession according to various variables. 64 students from Kafkas University Education Faculty Turkish Education Department 4. grade, and 60 students from the pedagogical formation program which is given at the same faculty, as a total 124 teacher candidates participated in this study. In this study "Attitude Measurement toward Teacher Profession" which is developed by Üstüner (2006) is used as data gathering tool. The gathered data is analyzed by SPSS 17.0 (Statistical Package for Social Sciences) package program. As a result of the study, it is found that the attitudes of teacher candidates toward teacher profession does not indicate a significant difference according to "under graduation department", "the department's order of preference in ÖSS", "gender", "the graduated high school" variables.